Perception of Endodontist /General dentists on Etiologies of file fracture associated with different types of rotary file systems. –A Questionnaire based cross sectional study - Dr Shalini Singh; Dr. Kailash Attur; Dr Neha Singh; Dr Anoop Samuel; Dr Sooriaprakas C; Dr Jansiya Thangavelu (The Bioscan, 2024)
Background: File fractures are a common complication in endodontic procedures, leading to increased treatment time and potential treatment failure. Understanding the etiologies of file fractures is crucial for developing effective prevention strategies. Objective: This study aimed to investigate the various factors contributing to file fractures, with a particular focus on TruNatomy file systems. The study compared the perceptions of endodontists and general dentists regarding the etiologies of file fractures and analyzed the factors associated with different types of rotary file systems. Methods: A non-probability convenience sampling of 2000 patients undergoing root canal treatment on mandibular first molars was conducted. Endodontists and general dentists (n=100 each) evaluated 10 cases using their standard NiTi system and TruNatomy file systems. Data was collected through online questionnaires and analyzed using parametric and non-parametric tests. Results: The study identified excessive pressure, over-usage of instruments, complex root canal anatomy, and incorrect insertion angles as common etiologies of file fractures. TruNatomy file systems were consistently associated with a higher risk of fracture due to excessive pressure and over-usage. Other file systems also exhibited varying levels of risk associated with specific factors. Conclusion: This study highlights the importance of preventive measures, including careful instrument selection, proper technique, and ongoing education, to reduce the risk of file fractures in endodontic procedures.